2011
DOI: 10.1371/journal.pgen.1002343
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity in Cytokines Associated with Immune Variation and Resistance to Multiple Pathogens in a Natural Rodent Population

Abstract: Pathogens are believed to drive genetic diversity at host loci involved in immunity to infectious disease. To date, studies exploring the genetic basis of pathogen resistance in the wild have focussed almost exclusively on genes of the Major Histocompatibility Complex (MHC); the role of genetic variation elsewhere in the genome as a basis for variation in pathogen resistance has rarely been explored in natural populations. Cytokines are signalling molecules with a role in many immunological and physiological p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
112
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(117 citation statements)
references
References 79 publications
5
112
0
Order By: Relevance
“…On the other hand, we analyzed FAS-L expression at the basal state, without stimulation in peripheral blood leukocytes. Besides differences in the protocols used for the analysis of gene expression, a combination of SNPs may affect the production of the molecule, 25 environmental agents can modify gene expression, 26 and different intracellular mechanisms may interfere with maintenance or degradation of mRNAs and proteins. 27 Indeed, several factors influence the production of a particular protein, and this influence can hinder the detection of a genotype/phenotype correlation.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, we analyzed FAS-L expression at the basal state, without stimulation in peripheral blood leukocytes. Besides differences in the protocols used for the analysis of gene expression, a combination of SNPs may affect the production of the molecule, 25 environmental agents can modify gene expression, 26 and different intracellular mechanisms may interfere with maintenance or degradation of mRNAs and proteins. 27 Indeed, several factors influence the production of a particular protein, and this influence can hinder the detection of a genotype/phenotype correlation.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in the present study, we detected a significant association between allele AA*05 and infection with Babesia ssp. Recently, Turner et al (2011) showed that the susceptibility to Babesia microti in common vole was associated with the variation within genes coding interleukines Il2 and Il2b.…”
Section: Effects Of the Mhc On Infection And Survival Ratesmentioning
confidence: 99%
“…To elucidate the evolutionary causes and consequences of such variation, a better understanding of which genes actually contribute to variation in resistance is desirable [2][3][4]. However, whereas there is a considerable body of literature on the genetic basis of resistance in humans [5], knowledge from other animals, and in particular from natural vertebrate populations, is as yet very limited (but see [6]). …”
Section: Introductionmentioning
confidence: 99%